A self-powered wearable seizure-monitoring/brain-stimulating system for potential epilepsy treatment. (March 2023) - Lin, Rui; Fan, Yaowei; Xie, Yan; Ge, Dengyun; Liang, Shan; Guan, Hongye; Chen, Meihua; Zhang, Yan; Xing, Lili; Xue, Xinyu; Zhan, Yang
Abstract: A new self-powered wearable body-detecting/brain-stimulating system for monitoring and restraining epilepsy has been fabricated. The system can monitor body motion in real time and transmit the stimulus signals to brain for restraining the epileptic seizures. The system is composed of energy harvesting module, the body motion detection sensor, the data processing center, and neural stimulator. An arch-shaped device made of piezoelectric ceramic transducer (lead zirconate titanate; PZT) as energy harvesting module can convert the mechanical energy generated by body movement into electricity power. The motion detection sensor is made of polyvinylidene fluoride (PVDF) doped with zinc oxide (ZnO) nanostructures, which can detect the tiny movements of the human body and transmit sensing signals to the data processing center. The data processing center can determine the epileptic seizure and generate neural stimulating signals. By stimulating the dentate gyrus/hilus brain region of mice, the total duration of epileptic seizures in mice is significantly reduced by 40–50%. This new self-powered strategy demonstrates the potential of brain-machine-interface system for personalized treatment of brain disease. Graphical Abstract: A self-powered wearable seizure-monitoring/brain-stimulating system for potential epilepsy treatment has been realized. Driven by body movement, this system can detect body motion in real time and transmit the stimulus signals to brain for restraining epileptic seizures. ga1 Highlights: New epilepsy treatment is realized by a self-powered wearable BMI system. The self-powered technique is introduced into a BMI system. It analyzes epilepsy seizure in real time and performs brain stimulation. A closed loop of behavior-system-brain is formed.